Avaliação eletrocardiográfica em camundongos (C57BL/6) com melanoma (B16F10) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Melanoma is a type of cancer with a high metastatic capacity and resistance to many treatments. Studies indicate that cancer can cause significant changes in the cardiovascular system, either due to disease progression or the treatment applied. Considering the importance of the electrocardiogram (ECG) in detecting arrhythmias and other cardiac abnormalities, this study aimed to understand how melanoma can impact cardiac function through electrocardiographic analyses. C57BL/6 mice were used, divided into control and melanoma groups. Melanoma was induced by injection of B16F10 cells, and the mice were monitored over 21 days, with electrocardiographic measurements taken every seven days. Non-invasive electrodes and a computerized veterinary electrocardiograph were used for the electrocardiographic evaluation, allowing for the analysis of parameters such as heart rate, amplitude, and duration of the P wave, QRS complex, as well as PR and RR intervals. The results showed that mice with melanoma exhibited significant changes in electrocardiographic parameters compared to the control group. Changes in heart rate, as well as in PR and RR intervals, and in the amplitude and duration of the P and R waves, were observed, indicating possible conduction dysfunctions associated with melanoma. These changes suggest that melanoma may have a direct impact on the heart's electrical conduction system, possibly due to the release of inflammatory cytokines or the effect of the tumor on cardiac metabolism. The presence of electrocardiographic changes in mice with melanoma reinforces the hypothesis that cancer can affect cardiac function. These results may contribute to a better understanding of the relationship between cancer pathophysiology and cardiovascular diseases, as well as provide a basis for the development of new therapeutic strategies aimed at protecting the heart during melanoma treatment.
Keywords: Melanoma; eletrocardiografia; camundongos C57BL/6; sistema cardiovascular; Melanoma; electrocardiography; C57BL/6 mice; cardiovascular system; CNPQ::CIENCIAS DA SAUDE